Analysis of Hotmix AC-WC Mixture Using Materials from Lagadar Quarry and Baleendah Quarry for Road Planning Design - Akbardin, Juang; Alpaqih, Nauval Fajar; Sekaryadi, Yudi (ASTONJADRO, 2025)
The material for the AC-WC hotmix mixture will affect the quality of the AC-WC hotmix itself. In the Bandung City area and its surroundings, materials for the AC-WC hotmix mixture are usually used which are taken from the Lagadar quarry and Baleendah quarry. Therefore, testing is carried out with the aim of comparing the quality of the material from which quarry is better between the two quarries. In addition, testing is needed on the asphalt that will be used because it will also affect the quality of the AC-WC hotmix asphalt produced, and testing is needed on the AC-WC hotmix sample itself by conducting a marshall test. Then the pavement thickness calculation is carried out using the AASTHO 1993 method to determine the thickness of the flexible pavement. Based on the results of the tests that have been carried out on the AC-WC hotmix mixture material taken from the two quarries, the results are quite good, both meet the required specifications. In addition, the test results on the 60/70 pen asphalt used also showed good results because all test results carried out met the specifications according to the existing SNI. The results of the marshall test on the two AC-WC hotmix samples produced showed good results. All marshall parameters for the two samples met the required specifications, but of the two AC-WC hotmix samples, the AC-WC hotmix sample with mixed material from the Baleendah quarry had better marshall parameter values.